The dose-response curve in cognitive-behavioral therapy for anxiety disorders. Issue 6 (1st November 2020) - Levy, Hannah C.; Worden, Blaise L.; Davies, Carolyn D.; Stevens, Kimberly; Katz, Benjamin W.; Mammo, Liya; Diefenbach, Gretchen J.; Tolin, David F.
ABSTRACT: Previous studies examining the dose-response curve in psychotherapy have suggested that 11–19 sessions may be necessary for at least 50% of individuals to show clinically significant improvement. However, this curve has not been examined specifically for cognitive-behavioral therapy (CBT) for anxiety disorders, for which a more rapid recovery curve may be expected. Survival analysis was used to assess the dose-response curve for 201 patients with anxiety disorders who received weekly CBT at an anxiety specialty clinic. The primary outcome measure was the Outcome Questionnaire-45.2, which patients completed prior to each treatment session. Sixty-four percent of the sample achieved reliable change, and this response occurred in approximately five sessions on average. Fifty percent of the sample achieved clinically significant improvement, which occurred in approximately eight sessions on average. The findings suggest that earlier response may be expected in CBT for anxiety disorders, and are discussed in terms of potential ways to further improve response rates for this treatment.